Downregulation of miR-211-5p Promotes Carboplatin Resistance in Human Retinoblastoma Y79 Cells by Affecting the GDNF–LIF Interaction - Ke, Ning; Chen, Lin; Liu, Qing; Xiong, Haibo; Chen, Xinke; Zhou, Xiyuan (Frontiers in Oncology, 2022)
Purpose To investigate the role of the miR-211-5p-GDNF signaling pathway in carboplatin resistance of retinoblastoma Y79 cells and what factors it may be affected by. Methods A carboplatin-resistant retinoblastoma cell line (Y79R) was established in vitro. RNA-seq and microRNA-seq were constructed between Y79 and Y79R cells. RNA interference, RT-PCR, Western blot (WB), and flow cytometry were used to verify the expression of genes and proteins between the two cell lines. The TargetScan database was used to predict the microRNAs that regulate the target genes. STING sites and Co-Immunoprecipitation (COIP) were used to study protein–protein interactions. Results GDNF was speculated to be the top changed gene in the drug resistance in Y79R cell lines. Moreover, the speculation was verified by subsequent RT-PCR and WB results. When the expression of GDNF was knocked down, the IC50 of the Y79R cell line significantly reduced. GDNF was found to be the target gene of miR-211-5p. Downregulation of miR-211-5p promotes carboplatin resistance in human retinoblastoma Y79 cells. MiR-211-5p can regulate the expression of GDNF. Our further research also found that GDNF can bind to LIF which is also a secreted protein. Conclusion Our results suggest that downregulation of miR-211-5p promotes carboplatin resistance in human retinoblastoma Y79 cells, and this process can be affected by GDNF–LIF interaction. These results can provide evidence for the reversal of drug resistance of RB.